1999
DOI: 10.1139/f99-022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stock-specific and environmental factors on the feeding migration of Atlantic salmon (Salmo salar) in the Baltic Sea

Abstract: Atlantic salmon (Salmo salar L.) stocks in the Baltic Sea are mainly exploited during their sea migration. The offshore fishery in the feeding grounds of these salmon permitted us to analyse the migrations of certain stocks on the basis of tag recovery data. Four salmon stocks from rivers draining into Bothnian Bay (25°E, 65.5°N) were selected for study. During 1984-1991, about 135 000 2-year-old hatchery-reared smolts were tagged and released. We applied logit models, with the site of recovery as a multicateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 14 publications
3
71
0
Order By: Relevance
“…Factors common to all stocks during the feeding migration include changes in the sea environment, such as the sea surface temperature, conditions in the feeding area, such as the availability of food, and the offshore and coastal fishery. This reasoning has proved correct in several previous studies related to salmon abundance, growth, and migration distance, in which synchronous trends have been related to common environmental factors [6,13,62,63]. The decrease in the proportion of old males has also been observed previous studies , as Järvi [64] reported approximately 11% of the spawners to be 4-6 SW salmon in the 1930s and 1940s, but an analysis sixty years later reported only 0.5-2% of salmon of that age [15].…”
Section: Spawning Age Variation Caused By the Natural Environmentmentioning
confidence: 63%
See 3 more Smart Citations
“…Factors common to all stocks during the feeding migration include changes in the sea environment, such as the sea surface temperature, conditions in the feeding area, such as the availability of food, and the offshore and coastal fishery. This reasoning has proved correct in several previous studies related to salmon abundance, growth, and migration distance, in which synchronous trends have been related to common environmental factors [6,13,62,63]. The decrease in the proportion of old males has also been observed previous studies , as Järvi [64] reported approximately 11% of the spawners to be 4-6 SW salmon in the 1930s and 1940s, but an analysis sixty years later reported only 0.5-2% of salmon of that age [15].…”
Section: Spawning Age Variation Caused By the Natural Environmentmentioning
confidence: 63%
“…The home rivers of all these stocks drain into the Bothnian Bay, the northernmost part of the Baltic Sea, and the stocks have very similar migration patterns. The fish from all these stocks undertake their feeding migration to the Baltic Main Basin, and return as spawners to their home rivers early in the summer, mainly during a few weeks in June [6,25].…”
Section: Salmon Stocksmentioning
confidence: 99%
See 2 more Smart Citations
“…In a tagging study over a period of 7 years, Kallio-Nyberg et al (1999) noted that environmental factors had a strong influence on migratory route in young Atlantic salmon and that prey abundance influenced migratory distances. Although our cluster results suggest that animals within clusters are influenced by coherent patterns of environmental variability, coho salmon may respond similarly and demonstrate interannual variability in spatial and temporal patterns of ocean utilization.…”
Section: Role Of Environmental Variation In Size and Survivalmentioning
confidence: 99%